Penyuluhan Dan Pelatihan Penginputan E-Rapor SMP Pada SMP NU 07 Brangsong - Dendy Kurniawan; Puteri Anindya Maulan; Ahmad Ashifuddin Aqham; Danang Danang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
As one of the efforts to care for the Community Service Institute (LPPM), namely by holding counseling training and training for inputting e-reports in 2022 so that it can facilitate the performance of Mr. and Mrs. Teachers at SMP NU 07 Brangsong. With this counseling and training program, it is hoped that educators can understand and implement the knowledge and information obtained to support the value management process to be good, fast and neatly documented. Based on the training that has been carried out, the following results are obtained. The teaching staff is able to understand the flow of the e-report value system.